2020
DOI: 10.1007/s11661-020-05781-6
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Grain Refinement by Machine Hammer Peening in High Deposition Rate Wire-Arc AM Ti-6Al-4V

Abstract: Surface deformation, applied in-process by machine hammer peening (MHP), has the potential to refine the coarse columnar b-grain structures normally found in high deposition rate Wire-Arc Additive Manufacturing (WAAM) processes with Ti alloys like Ti-6Al-4V. Effective refinement, as well as a reduction in texture strength, has been achieved in relatively thick sections and to a depth that is greater than that expected from the surface deformation induced by MHP. By application of MHP to each deposition track, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 40 publications
(68 reference statements)
2
22
0
Order By: Relevance
“…The same is true with the shot peening on an as-printed aluminum alloy AlSi10Mg [40]. These functionally flexible methods [36][37][38][39][40] were almost as effective as rolling.…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…The same is true with the shot peening on an as-printed aluminum alloy AlSi10Mg [40]. These functionally flexible methods [36][37][38][39][40] were almost as effective as rolling.…”
Section: Introductionmentioning
confidence: 65%
“…Hammer peening is applied to modify the subsurface structures by severe plastic deformation with subdivision and misorientation in the previously grown grains, and eliminate the growth textures and large columnar grains [36,37]. Surface modification processes such as cavitation peening, shot peening and laser peening methods were applied on Ti-6Al-4V samples fabricated with the use of direct metal laser sintering and electron beam melting [38], achieving 70-97% improvement in fatigue strength.…”
Section: Introductionmentioning
confidence: 99%
“…CHP is an impact based process in which the impact energy is provided by the kinetic energy of an oscillating tool. Hönnige et al [29] and Kumar et al [30] have shown that shock waves from CHP produces grain refinement in the component inducing microstresses near the surface. The CHP treatment resulted in a much higher degree of compaction (i.e., percentage reduction of the coating thickness after the treatment), as shown in Figure 10, of the sprayed coating (in comparison to DCR).…”
Section: Discussionmentioning
confidence: 99%
“…Inter-pass deformation can be implemented by using techniques such as rolling [18], or peening [19], to deform the surface of the deposit before the next layer/melt track is applied. In this approach the stored energy from the inter-pass deformation, combined with the heat input from subsequent deposition passes, results in β recrystallization during reheating through the β transus [20]. This method is attractive as there is no change in the alloy composition; however, it adds an additional processing step which slows production time.…”
Section: Introductionmentioning
confidence: 99%